2006
DOI: 10.1111/j.1742-4658.2006.05583.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cobalamin‐dependent methionine synthase by substituted benzo‐fused heterocycles

Abstract: The cobalamin–dependent cytosolic enzyme, methionine synthase (EC.2.1.1.13), catalyzes the remethylation of homocysteine to methionine using 5‐methyltetrahydrofolate as the methyl donor. The products of this remethylation – methionine and tetrahydrofolate – participate in the active methionine and folate pathways. Impaired methionine synthase activity has been implicated in the pathogenesis of anaemias, cancer and neurological disorders. Although the need for potent and specific inhibitors of methionine syntha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Side effects could potentially be mitigated by rescue therapy, perhaps with leucovorin, as is common for other anti-folates. To our knowledge, no clinically approved antifolate therapies are known to directly inhibit MTR, though some low potency, folate-like small molecule inhibitors have been reported [50][51][52]. We look forward to the advancement of such compounds into in vivo tools so that the therapeutic potential of MTR inhibition can be more rigorously evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Side effects could potentially be mitigated by rescue therapy, perhaps with leucovorin, as is common for other anti-folates. To our knowledge, no clinically approved antifolate therapies are known to directly inhibit MTR, though some low potency, folate-like small molecule inhibitors have been reported [50][51][52]. We look forward to the advancement of such compounds into in vivo tools so that the therapeutic potential of MTR inhibition can be more rigorously evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Obtained as a brown solid (39.6 mg, 99%). mp 155−164 °C (reported 53 54 2-Methyl-6-Benzoxazolamine (2ab). Purified by column chromatography using hexane/EtOAc = 3:1 as eluent.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…This led to the discovery of metronidazole, which targets DNA in anaerobe bacteria without antagonistic effects in combination with isoniazid or rifampicin [49]. Other studies identified methionine synthesis, important for nucleotide and protein synthesis, as a viable target, as human cells do not synthesize this amino acid [50,51]. The permeability of the cell wall can be influenced by a diverse range of compounds.…”
Section: Metabolite Profiling a “New” Approach For Drug Discoverymentioning
confidence: 99%